Immobilization of enzymes into self-assembled iron(III) hydrous oxide nano-scaffolds: A bio-inspired one-pot approach to hybrid catalysts - Bellino, Martin Gonzalo (2011)
A simple bio-inspired one-pot procedure for the immobilization of α-amylase into maturing hybrid iron(III) hydrous oxide nanostructures is described. The method resorts to the urease mediated decomposition of urea to induce the homogeneous precipitation of amylase-iron(III) hydrous oxide ensembles. Appropriate setting of the synthesis parameters, which control the shape and texture of the resulting hybrid nanostructures, is key to amylase entrapment. Highly efficient hybrid catalysts were prepared at the lowest urease concentration (0.5 mg/mL), where spherical 100 nm size hybrid iron(III) hydrous oxide ensembles formed; their amylase load depended on the enzyme concentration, in a michaelian fashion. Their specific activity is nearly that of free amylase. These catalysts are reusable, with no loss of performance, and substantially more active than the free enzyme at extreme pHs and temperatures. The high efficiency of the hybrid ensembles is ascribed to their open structure, high enzyme loading, and negligible amylase inactivation.